Temporal characteristics and energy deposition of pulsating auroral patches. Issue 7 (23rd July 2016) - Humberset, B. K.; Gjerloev, J. W.; Samara, M.; Michell, R. G.; Mann, I. R.
Abstract: We present a careful statistical analysis of pulsating aurora (PA) using all‐sky green line (557.7 nm) images obtained at 3.3 Hz. Six well‐defined individual PA patches are identified and extracted using a contouring technique. Quantitative parameters such as the patch duration (on‐time and off‐time), peak intensity, and integrated intensity are determined for each patch and each pulsation. The resulting characteristics serve as strict observational constraints that any of the many competing theories attempting to explain PA must predict. The purpose of this paper is to determine the characteristics of PA patches in order to provide better observational constraints on the suggested mechanisms. All aspects of the temporal behavior of the individual patches appear to be erratic. Historically, PA has been defined very loosely and we argue that the use of the term "pulsating" is inappropriate since our findings and other published results are not regularly periodic and thus a more appropriate term may be fluctuating aurora. Further, we find that the observational constraints do not fit well with the flow cyclotron maser theory, which in particular is suggested to create PA patches. There is no clear candidate of the suggested mechanisms and drivers to explain the observational constraints set by the PA patches in a satisfactory manner. Key Points: Objective and quantitative characteristics of pulsating auroral patches Pulsating aurora is highly variable in all measurable parameters and thus would be more accurately described as fluctuating aurora Characteristics of pulsating auroral patches do not fit well with the flow cyclotron maser theory